Charging Ahead: The Evolution and Reliability of Nickel‐Zinc Battery Solutions - Idris Temitope Bello; Hassan Raza; Alabi Tobi Michael; Madithedu Muneeswara; Neha Tewari; Wang Bingsen; Yin Nee Cheung; Zungsun Choi; Steven T. Boles (EcoMat)
ABSTRACT Nickel‐Zinc (Ni‐Zn) batteries offer an interesting alternative for the expanding electrochemical energy storage industry due to their high‐power density, low cost, and environmental friendliness. However, significant reliability challenges such as capacity fading, self‐discharge, thermal instability, and electrode degradation detract from their competitiveness in the market, hindering their widespread adoption. This study thoroughly examines the degradation mechanisms and approaches to improve the reliability of Ni‐Zn batteries: Starting with their basic chemistry, operating principles, and degradation pathways, strategies for improvement are explored including material modification, electrolyte optimization, cell design approaches, and thermal management techniques. Advanced characterization methods for data collection and reliability assessment are discussed, including electrochemical, structural, spectroscopic, and in situ techniques which are noted for their ability to identify key areas of concern for this cell chemistry. We further consider emerging trends such as novel materials, hybridization with other energy technologies, and the challenges of large‐scale implementation, emphasizing the need for standardized reliability testing protocols. Opportunities for the integration of advanced sensing, such as fiber Bragg grating (FBG) sensors for real‐time monitoring and anomaly detection, along with machine learning (ML) and prognostics and health management of Ni‐Zn batteries are highlighted, as these open the door to future research directions. This comprehensive review should serve as a resource for researchers, engineers, and industry experts aiming to advance and commercialize dependable, high‐performing Ni‐Zn battery technology for a sustainable energy future.